Smooth muscle cell transient receptor potential polycystin‐2 (TRPP2) channels contribute to the myogenic response in cerebral arteries. (15th August 2013) - Narayanan, Damodaran; Bulley, Simon; Leo, M. Dennis; Burris, Sarah K.; Gabrick, Kyle S.; Boop, Frederick A.; Jaggar, Jonathan H.
Key points:   Intravascular pressure is reported to activate several mechanosensitive ion channels, leading to smooth muscle cell (SMC) depolarization, voltage‐dependent Ca 2+ channel activation and vasoconstriction; a process known as the 'myogenic response'.   Polycystin‐1 and ‐2 (TRPP1 and ‐2) have been shown to differentially regulate the mesenteric artery myogenic response, with TRPP2 expression attenuating vasoconstriction.   We show that TRPP2 is the major TRPP isoform expressed and that TRPP2 is located primarily in the plasma membrane in cerebral artery SMCs.   Selective TRPP2 knockdown reduced swelling‐induced non‐selective cation currents ( I Cat ) in SMCs and myogenic tone in cerebral arteries.   These data indicate that TRPP2 activation contributes to the cerebral artery myogenic response and suggest that TRPP2 performs differential functions in different vascular beds. Abstract  Intravascular pressure‐induced vasoconstriction is a smooth muscle cell‐specific mechanism that controls systemic blood pressure and organ regional blood flow. Smooth muscle cell polycystin‐1 and ‐2 (TRPP1 and ‐2) proteins modulate the myogenic response in mesenteric arteries, but involvement in other vascular beds is unclear. Here, we examined TRPP2 expression, cellular distribution, cation currents ( I Cat ), and physiological functions in smooth muscle cells of rat and human cerebral arteries. We demonstrate that TRPP2 is the major TRPP isoform expressed in cerebral artery smooth muscle cells, with message levels higher than those of TRPP1. Arterial biotinylation and immunofluorescence indicated that TRPP2 is located primarily (∼88%) in the smooth muscle cell plasma membrane. RNA interference reduced TRPP2 expression by ∼55% compared to control, but did not alter levels of TRPP1, TRPC1, TRPC3, TRPC6, TRPM4, ANO1/TMEM16A, or voltage‐dependent Ca 2+ (CaV 1.2) channels, other ion channel proteins that modulate myogenic tone. Cell swelling induced by hyposmotic (250 osmol (l solution) −1 ) bath solution stimulated Gd 3+ ‐sensitive I Cat in smooth muscle cells that were reduced by selective TRPP2 knockdown. TRPP2 knockdown did not alter myogenic tone at 20 mmHg but reduced tone between ∼28 and 39% over an intravascular pressure range between 40 and 100 mmHg. In contrast, TRPP2 knockdown did not alter depolarization‐induced (60 mmol l K + ) vasoconstriction. In summary, we show that TRPP2 is expressed in smooth muscle cells of resistance‐size cerebral arteries, resides primarily in the plasma membrane, and contributes to the myogenic response. Data also suggest that TRPP2 differentially regulates the myogenic response in cerebral and mesenteric arteries.